Observing Optional Number in DDC Edition 23 - Rotmianto, Mohamad (Universitas Airlangga, 2015)
Dewey Decimal Classification is a most popular classification system in the world because of its completeness and most up-to-date. There are many optional number in this classification system, although it rarely to be discussed even it is important to known well about that optional number, especially Â for Â a Â librarian Â as Â classifier. Â This Â paper Â is Â a Â literature Â study Â about Â Dewey Â Decimal Classification Â Edition Â 23, Â to Â describe Â about Â optional Â numbers, Â particularly Â the Â number Â in relationship with Indonesiaâs subject and discipline. This paper is to avoid misunderstanding in interpreted about optional number among librarians, especially for who that does not understand well about optional numbers.